The last boyfriend [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Inn BoonsBoro trilogy, 2012)
The historic hotel in Boonsboro, Maryland, has endured war and peace, changing hands, even rumored hauntings. Now it's getting a major facelift from the Montgomery brothers and their eccentric mother. As the architect of the family, Beckett's social life consists mostly of talking shop over pizza and beer. But there's another project he's got his eye on: the girl he's been waiting to kiss since he was fifteen ...